Sustentabilidade : a usucapião coletiva urbana sob o olhar do direito ambiental - Freitas, Paulo Cosme de (2012)
As a social right, the right to housing is part of the dimension of fundamental rights and, in consequence, the State requires affirmative action towards its achievement. More than a roof over their heads, the right to housing includes the promotion of basic infrastructure and adequate, the quality of the natural and urban environments. Moreover, the Federal Constitution, in Article 225, first sentence, also establishes the right and duty of solidarity of the State and individuals in preserving the environment for present and future generations. This paper investigates how the institution of collective urban adverse possession, expected in the City Statute, can function as an instrument of urban policy for the environmental regulation of the areas affected by the slums, guaranteed housing, but also the necessary contemplation of constitutional right to an ecologically balanced environment. From a multidisciplinary perspective, with the sources underpinning the dialogue, this work starts from the realization of human rights, since the plane of international law, going to the fundamental rights, at home, to get to the Institute of collective urban adverse possession, positive in the Statute City and understand how it can serve to regulate land and environmentally conglomerates such informal and face the problem of occasional tension between the fundamental right to housing and the fundamental right to an ecologically balanced environment.